1964
DOI: 10.1111/j.1537-2995.1964.tb02900.x
|View full text |Cite
|
Sign up to set email alerts
|

A “New” Rh Antibody (Anti‐Rh 26) which Detects a Factor Usually Accompanying hr‘

Abstract: A aerum (J.D.) obtained from a donor of type RhlRh,(CCDee.) was determined by the usual atudies to be anti-hr'(c). It was eventually found, however, to give no reaction with an occarional blood sample which was hr'-pitive with all other typing serums. Cells of the latter phenotype (J.U.negative, hr'-positive) rhow a weakened expression of both hr' and hr(f). The characteristic is inherited, is expressed in the heterozygote, and has not yet been found in the hamozygoua form. The J.D. aerum has been designated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…RBCs with altered Rhce and considered to be hr S − included ceAR, ceBI, ceEK, and ceMO, and those considered to be hr B − included ce S (encoded by RHCE * ce 48C, 733G, 1006T ), ceMO, 1,12 and (C)ce S (r′ S ) 1 . Partial c antigens have been reported to be associated with RH:−26, (C)ce S , ce S (340), and ceAR 13‐20 . We have shown here that RhceCF expresses partial c and e antigens.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…RBCs with altered Rhce and considered to be hr S − included ceAR, ceBI, ceEK, and ceMO, and those considered to be hr B − included ce S (encoded by RHCE * ce 48C, 733G, 1006T ), ceMO, 1,12 and (C)ce S (r′ S ) 1 . Partial c antigens have been reported to be associated with RH:−26, (C)ce S , ce S (340), and ceAR 13‐20 . We have shown here that RhceCF expresses partial c and e antigens.…”
Section: Discussionsupporting
confidence: 56%
“…1 Partial c antigens have been reported to be associated with RH:-26, (C)ce S , ce S (340), and ceAR. [13][14][15][16][17][18][19][20] We have shown here that RhceCF expresses partial c and e antigens. Each of the previously mentioned alleles encodes a different phenotype and the alloanti-c and/or anti-e are not expected to be mutually compatible.…”
Section: Discussionmentioning
confidence: 99%
“…All four samples were tested by a one‐stage papain capillary test with the original examples of anti‐Rh26 (J.D. ) 21 and anti‐LOCR (Cr. ) 18 and by the capillary indirect antiglobulin method with a monoclonal antibody (BS240) 22 originally thought to be anti‐c.…”
Section: Methodsmentioning
confidence: 99%
“…One, an alloanti-c in a c+ (presumed phenotype R 1 r) person, was reported by Moulds and coworkers [2]. The other was anti-Rh26, which can appear as anti-c, and has been made by a Rh26−, c− person [3] and also by a RH26−, c+ person [4]. Molecular studies have shown that Rh26 is antithetical to the low-prevalence antigen LOCR and serological studies have shown that the LOCR+ phenotype encodes altered (weakened) expression of c [5].…”
Section: Introductionmentioning
confidence: 93%